Budaya Minangkabau: Peradaban Dan Nilai-nilai Pendidikan Generasi Baru - Zulfa Zulfa; Livia Ersi (Bakaba : Jurnal Sejarah, Kebudayaan dan Kependidikan, 2021)
The problems that occur in the world of higher education at this time are very alarming. One of them is a PhD student in the UK. Cases that tarnish the world of education at the international level. The purpose of this study is to describe civilization and educational values for the new generation so that the moral problems that occur in Indonesia can be reduced. This research method is a qualitative research with a historical and sociological approach. The results of this study indicate that with local culture civilization and educational values will be realized for the better. The local culture is Minangkabau Culture from elementary school to university level. This is very important so that the ideal character education can be realized in accordance with the 18 character values based on the National Education System Law. Minangkabau Culture Learning in Higher Education is carried out using the Simulation Project-Based Learning (PBPS) model. PBPS is a project or task-based learning that is directly applied in the form of a simulation for each student. In this study, there are no exams, only simulations and practicals so that students can understand every custom and procession that is simulated so that the ideal character improvement can be realized. Using PBPS learning will provide independence for students to identify character values that come from the values of life in the family environment or in Minangkabau society.